The Added Value of an Intentional Training - Refiya Scheltinga; Eveke De Louw; Claudia Bulnes (Forum Neue Medien in der Lehre Austria, 2017)
The increased need to intentionally develop intercultural competence through the curriculum is high on the agenda of institutions of higher education. The purpose of this article is to demonstrate that a compulsory study abroad experience can be meaningful and effective for intercultural competence development when it is embedded in the larger context of the formal curriculum of a degree programme. The research explores the relationship between a study abroad with an intentional intercultural training and the development of intercultural sensitivity. The training is facilitated through pre-departure sessions, reflective essay writing and a re-entry session. Cultural mentors provide support and feedback on the reflective tasks. CHEN & STAROSTA's Intercultural Sensitivity Scale (2000) was used to explore levels of intercultural sensitivity after study abroad. Instead of the widely used pre-post test, this study administered a post-then test. Both the test group and the control group showed increased levels of intercultural sensitivity after study abroad. The test group that received an intentional intercultural training before, during and after study abroad showed a significantly higher level of intercultural sensitivity than the control group in both the then and post test.